1988
DOI: 10.1002/glia.440010202
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression of glial fibrillary acidic protein and vimentin in the central and peripheral nervous systems of the twitcher mutant

Abstract: A method to purify glial fibrillary acidic protein (GFAP) from mouse spinal cord is described, which permits the measurement of GFAP in the sciatic nerve of the twitcher mutant and control mouse. Cytoskeletal proteins from sciatic nerves and purified GFAP standards were electrophoresed on gel, transferred to nitrocellulose paper, and immunostained with anti-GFAP antibody. From the immunostained, 51,000-dalton band, we estimated about 200 ng GFAP per 50 micrograms of cytoskeletal protein in the twitcher sciatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…As previously reported (Chiu et al, 1988), each cytoskel-eta1 pellet, containing 2-3.5 mg protein, was solubilized in 1 ml of 30 mM sodium phosphate buffer, pH 7.5, containing 6 M urea, 2 mM EGTA, 0.5 mM PMSF, 1% (vol/vol) 6-mercaptoethanol, and 1 .O pg/ml leupeptin, and passed through a 0.5-ml column of CM-52 (Whatman Ltd., Kent, England) to remove histones and other low-molecular weight basic proteins. The eluent (approximately 2.5 ml) was injected into a FPLC-Mono Q column (anionic exchanger), 5 X 50 mm (Pharmacia, Piscataway, NJ, U.S.A.), and developed with a 25-ml gradient of 0 to 0.6 MNaCl in the above buffer at a flow rate of 0.5 ml/min.…”
Section: Purification Of Gfap By Fplcsupporting
confidence: 72%
See 1 more Smart Citation
“…As previously reported (Chiu et al, 1988), each cytoskel-eta1 pellet, containing 2-3.5 mg protein, was solubilized in 1 ml of 30 mM sodium phosphate buffer, pH 7.5, containing 6 M urea, 2 mM EGTA, 0.5 mM PMSF, 1% (vol/vol) 6-mercaptoethanol, and 1 .O pg/ml leupeptin, and passed through a 0.5-ml column of CM-52 (Whatman Ltd., Kent, England) to remove histones and other low-molecular weight basic proteins. The eluent (approximately 2.5 ml) was injected into a FPLC-Mono Q column (anionic exchanger), 5 X 50 mm (Pharmacia, Piscataway, NJ, U.S.A.), and developed with a 25-ml gradient of 0 to 0.6 MNaCl in the above buffer at a flow rate of 0.5 ml/min.…”
Section: Purification Of Gfap By Fplcsupporting
confidence: 72%
“…Assuming similar findings throughout the length of the spinal cord, this suggests that the decline of vimentin with diminishing inflammation may be balanced by an increase of vimentin in a subpopulation of reactive astrocytes. Others have noted that only a minority of reactive astrocytes in a number of gliotic conditions contain vimentin (Dahl et al, 198 1 ;Pixley and devellis, 1984;Schiffer et al, 1986;Chiu et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We noted previously that vimentin was elevated in chronic relapsing S J W mice (Smith and Eng, 1987), and Aquino et al (1988) found these levels to increase, following a time course similar to that of GFAP. It is likely that some vimentin was contributed by the inflammatory cells (Eng et al, 19861, but co-expression of GFAP and vimentin has been demonstrated in some, but not all, astrocytes from brain of various pathologic conditions (Calvo et al, 1991;Chiu et al, 1988;Dahl et al, 1981;Schiffer et al, 1986). Although vimentin mRNA was not measured here, it is likely to be upregulated on a schedule similar to that of GFAP.…”
Section: Discussionmentioning
confidence: 99%
“…As the cells of the astrocyte family mature, vimentin is gradually replaced by intermediate filaments composed of the more specific GFAP (Dahl, 1981;Pixley and De Vellis, 1984). In glial cultures (Chiu et al, 1981;Fedoroff, 1986) or under pathological conditions (Chiu et al, 1988;Paulus and Roggendorf, 1988;Pixley and De Vellis, 1984;Sharp et al, 1982), vimentin synthesis may persist or may be resumed, resulting in astrocytes that express both filament proteins simultaneously. It is therefore not surprising that our cultures contained both vimentin single-labeled and vimentidGFAP double-labeled cells and relatively large amounts of both proteins.…”
Section: Discussionmentioning
confidence: 99%